Kesalahan Penulisan Kata-Kata Momentum dalam Bahasa Indonesia: Studi Berbasis Korpus - Icuk Prayogi; Ikmi Nur Oktavianti (Institut Agama Islam Negeri Curup, 2025)
Many temporal terms in human life are frequently misspelled, particularly on the internet. This study aims to investigate the extent to which these temporal terms have been incorrectly written. The methodology involves querying the largest Indonesian digital corpus with specific queries based on commonly misspelled temporal terms in daily usage. This corpus-based analysis is intended to ensure empirical and measurable data. The study's findings indicate that errors in writing these temporal terms can be classified into spelling errors, capitalization errors, and spacing errors. Upon classification and quantification, it was found that the majority of these errors are associated with religious terms, such as Ramadan and zuhur, which are often written incorrectly. Errors were also found in the use of the preposition di replacing pada for indicating time and the use of jam instead of pukul. This study emphasizes the need for evaluation in language education and outreach to improve public understanding of standard spelling